Critias - Plato, 428? BCE-348? BCE; Jowett, Benjamin, 1817-1893 (Salt Lake City, UT : Project Gutenberg, 1998)
"Critias" by Plato is a dialogue written in ancient Greece that recounts the legendary story of Atlantis, a mighty island kingdom that attempted to conquer Athens. Through the character Critias, Plato describes how the gods divided the ancient Earth and how early Athens embodied an ideal civilization of virtue and moderation. The dialogue contrasts a good city with one corrupted by ambition, exploring themes of divine justice and societal decline. Part of an unfinished trilogy, the work ends abruptly, leaving Atlantis's fate tantalizingly incomplete. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Critias_(dialogue)
Release date is 1998-12-01
Produced by Sue Asscher, and David Widger
Keywords: Classical literature